Can agricultural extension and input support be discontinued? Evidence from a randomized phaseout in Uganda - Fishman, Ram; Smith, Stephen C.; Bobić, Vida; Sulaiman, Munshi (MIT Press, 2024)
This article was published in The Review of Economics and Statistics [©2022 Rights managed by MIT Press] and the definite version is available at: https://doi.org/10.1162/rest_a_01029 The Article's website is at: https://direct.mit.edu/rest/article-abstract/104/6/1273/98193/Can-Agricultural-Extension-and-Input-Support-Be?redirectedFrom=fulltext